Readout interfacing circuit for ISFET ionic concentration measurements / Turki Abdulmajid Abdo Alqutami - Abdo Alqutami, Turki Abdulmajid (2013)
ISFET, ion sensitive field effect transistor, is an electrochemical sensor that detects ionic concentrations in the material. Those detected ions will results in a change of the threshold voltage (Vth) of ISFET. The ISFET that was chose for this research was a PH ISFET sensor. The changes in Vth of ISFET will be interpreted by a read-out interfacing circuit (ROIC) that is called CVCC, constant-voltage constant-current. The circuit will show the changes of Vth as variations in the output voltage (Vout). In order to measure the Vout from ROIC, it is connected to a microcontroller based-system that measures the output voltage though a voltmeter Temperature and time is calculated using different sensors. The softwares used were LTspice for simulation, Proteus and Arduino microcontroller. The ROIC was tested under different parameters value of the circuit. Some parameters had an effect of increasing or decreasing on the output voltage from ROIC. The ISFET sensor itself had been investigated under different conditions. It was observed that ISFET is affected by temperature and its fabrication characterization